Small bite closure in midline laparotomy; A practice to reduce the surgical site infection, wound dehiscence, and incisional hernia - Hassan, Yaqoob; Arajmand, Shah; Wani, Anayatullah; Gilkar, Ishfaq; Shah, Syed (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Background: Postoperative wound site complications are a significant source of morbidity after midline laparotomy. The study's objectives were to compare the two suture patterns for fascial closure in midline abdominal wounds and their effect on postoperative wound site complications. Materials and Methods: Over 4 years, the prospective comparative study was conducted at the Government Medical College Hospital, Srinagar. All the patients ≥18 years and ≤70 years of age underwent midline laparotomy for various indications were included. Patients were randomized to two groups using computer-generated numbers based on closure techniques. Group A; Large Tissue Bite closure (10 mm from the wound edge and 10 mm apart and Group B; Small Tissue Bite closure (5–7 mm from the wound edge and 5–7 mm apart). Effect of age, sex, body mass index (BMI), albumin, and suture bite on postoperative complications were analyzed. Results: Among 324 patients who met the inclusion criteria, the mean age was 39.17 years, 84.56% were male with a Male: Female ratio of 5.48. Two hundred and two (62.35%) patients had large tissue bite closure, and 122 (37.75%) had small bite closure. There was no statistically significant difference between the two groups concerning age, sex, albumin levels, BMI, and type of surgery. About 35.64% of patients in the large tissue bite closure group and 19.67% patients in small bite closure developed surgical site infection (SSI) (P = 0.002). The difference in wound dehiscence between the two groups (15.84% vs. 7.38%) was statistically insignificant (P = 0.29). In midline laparotomy closure, the small bites technique results in significantly less incisional hernias than the large bites technique (P = 0.00001). None of our patients expired during the study period. Conclusion: The small bite technique substantially reduces SSIs, wound dehiscence, and incisional hernia. The accident-emergency and general surgery residents, in particular, should be made familiar with this technique to avoid postoperative wound site complications and improve the quality of postoperative life.
Keywords: Complications; laparotomy; midline incision; small bite closure; suture technique